Topological Magnetic Solitons on a Paraboloidal Shell - Altbir-Drullinsky, D; Elias-Moreno, R; Carvalho-Santos, V (Elsevier B.V., 2015)
We study the influence of curvature on the exchange energy of skyrmions and vortices on a paraboloidal surface. It is shown that such structures appear as excitations of the Heisenberg model, presenting topological stability, unlike what happens on other simply-connected geometries such as pseudospheres. We also show that the skyrmion width depends on the geometrical parameters of the paraboloid. The presence of a magnetic field leads to the appearance of 2π-skyrmions, introducing a new characteristic length into the system. Regarding vortices, the geometrical parameters of the paraboloid play an important role in the exchange energy of this excitation. © 2014 Elsevier B.V.